Nursing Care to Meet Fluid and Electrolyte Needs of Chronic Kidney Disease Patient - Tasya Shafa Rahman; Sri Utami Dwiningsih; Nina Indriyawati (Poltekkes Kemenkes Semarang, 2021)
Background: Chronic Kidney Failure (CKD) is a kidney function disorder that occurs gradually, cannot be recovered, and describes a decrease in urine production which results in an accumulation of fluid in the body. This can disrupt their fluid and electrolyte balance. In this regard, in Indonesia there are still many phenomena of non-compliance with fluid monitoring that occur. If this is left unchecked, it will result in a condition of overload or excess fluid in the patient. Fluid management is needed to fulfill the patient's fluid and electrolyte needs, so that changes in body weight and the results of the calculation of fluid balance can be controlled and become an illustration of meeting these needs.Purpose: to explain nursing care to meet fluid and electrolyte needs in chronic kidney disease patients.Methods: nursing care was carried out on patients with a diagnosis of chronic kidney disease who have impaired fluid and electrolyte requirements. The nursing intervention used to overcome this problem was fluid management. Data were collected from interviews and observations and further analysis was carried out.Results: After three days nursing intervention, the results showed that the client's level of shortness of breath decreased, the blood pressure level was close to normal, fluid calculation close to balance, and the client's weight seemed stable.Conclusion: fluid management was effective for monitoring fluid intake and output of chronic kidney disease patient.